Creativity, Proactive Personality, and Entrepreneurial Intention: The Role of Entrepreneurial Alertness - Hu, Rui; Wang, Li; Zhang, Wei; Bin, Peng (Frontiers in Psychology, 2018)
This study examines the extent to which entrepreneurial alertness mediates the effects of students’ proactive personalities and creativity on entrepreneurial intention. Drawing on a field survey of 735 Chinese undergraduates at 26 universities, this study provides evidence for the argument that entrepreneurial alertness has a fully mediation effect on the relationship between creativity, a proactive personality, and entrepreneurial intention. The findings shed light on the mechanisms that underpin entrepreneurial alertness and contribute to the literature on key elements of the entrepreneurial process.